Pendidikan Agama Kristen Memerangi Kekerasan Seksual Terhadap Anak Dalam Keluarga - Lekahena, Welly Sany (STT Pelita Dunia, 2024)
Abstract: Increasing news about child sexual abuse in the mass media has shocked many people. society is shocked. Cases of child sexual abuse within the family are still being reported. Children who are victims of sexual violence sexual violence in the family need to be protected and not victimized by parents, because sexual violence experienced by children will have an impact on their health. parents, because sexual violence experienced by children will have a negative impact on their growth and development, especially on their psychology and development. on their growth and development, especially on the psychology and mentality of the child. psychology and mentality of the children themselves. Children who are the next generation of the church and also the nation need to be educated and protected from an early age. Because if many children who feel and experience sexual violence, it is possible that the child will become a perpetrator of sexual violence in the days to come or in the future. perpetrators of sexual violence in the days to come or when they are adults. The purpose of this study is to provide an understanding of Christian religious education related to the responsibility of parents as representatives of related to the responsibility of parents as God's representatives in the family, not as perpetrators of sexual violence for children. family not as perpetrators of sexual violence for children. This research This research uses a literature study method in which the information or results summarized are obtained from various sources, namely the internet, television, journals and other sources. summarized from various sources, namely the internet, television, journals and other media. other media.